Changing the design of electric motors transport systems in order to save energy resources of autonomous power supplies - Журиленко, Б.Є.; Ніколаєв, К.І.; Ніколаєва, Н.К. (Science-based technologies, 2018)
In the article the possibility of modernization the design of an electric motor for a hybrid vehicle, an unmanned aerial vehicle (UAV), an aircraft and other transport systems in order to save the energy resources of an autonomous power supply are considered. Theoretically, the possibility of saving energy in the case of constant traction and rotor speed of the electric motor or increasing traction power with constant electromagnetic moment is shown. The constructional changes of the motor, specifically adjusting the radius of rotor to exceed the radius of the thruster, lowers the energy consumption of the motor and by that increases its operational time while keeping the same power source. The variants of modernization of electric motors for UAVs and planes, as well as electric vehicles for increasing energy saving in transport are offered.